Drawing as language in design project: a course of analysis via Vesely and Perez-Gomez - Magalhães, Graça Maria Alves dos Santos (2014)
We propose drawing as design project process, regarded both as project’s instrumental utility (technology) and condition for disciplinary reflection (art), considering drawing as language whose operability enables innovation in design. At the production level (drawing), two cornerstone conditions are implied: 1. the instrumental ability (technology) and 2. its critical (semantical) evaluation. As subject for analysis we present project drawings from widely recognized contemporary Portuguese designers. We interpret design object as the project’s overall communication exchange, questioning how drawing, as mediator for projectual practice in design, limits the object’s creation and hence its existence as design language? Our answer considers drawing: 1. mediator for representation (through technical expression), 2. classifying function (through program) and 3. interpretative mark of imagination (through authorship).